Daily Negative Work Events and Employees' Physiological and Psychological Reactions - Volmer, Judith; Fritsche, Andrea (Frontiers in Psychology, 2016)
Scholars have accumulated an abundant amount of knowledge on the association between work stressors and employees’ health and well-being. However, notions of the complex interplay of physiological and psychological components of stress reactions are still in their infancy. Building on the Allostastic Load (AL) model, the present study considers short-term within-person effects of negative work events (NWEs) on indicators of both physiological (i.e., salivary cortisol) and psychological distress responses (i.e., negative affect and emotional exhaustion). Multilevel findings from an experience sampling study with 83 healthcare professionals suggest that reported NWEs predict employees’ psychological but not endocrine stress responses. Results contribute to a more comprehensive understanding of employees’ daily response patterns to occupational stressors.